2018
DOI: 10.1177/1352458518772748
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rituximab in refractory RRMS

Abstract: This study provides level IV evidence that rituximab reduces clinical and MRI disease activity in patients with active RRMS despite immunosuppressive DMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…Accordingly, the B celldepleting agent rituximab has found to be a successful application both in conditions caused by pathogenic autoantibodies, such as autoimmune thrombotic thrombocytopenic purpura and hemolytic anemia, as well as in diseases presumably driven by autoreactive T lymphocytes, such as progressive multiple sclerosis and rheumatoid arthritis. [33][34][35][36][37] Rituximab is also highly effective in patients with IgG 4 -RD, a primarily fibrotic disorder in which the relevance of autoantibodies and T cells to fibrosis is still being explored. 5,38 Our recent studies have implicated antibodies to galectin-3 in a subset of patients with IgG 4 -RD, and others have identified autoantibodies to a recombinant truncated form of laminin 511, but definitive proof of a pathogenic role of these antibodies has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the B celldepleting agent rituximab has found to be a successful application both in conditions caused by pathogenic autoantibodies, such as autoimmune thrombotic thrombocytopenic purpura and hemolytic anemia, as well as in diseases presumably driven by autoreactive T lymphocytes, such as progressive multiple sclerosis and rheumatoid arthritis. [33][34][35][36][37] Rituximab is also highly effective in patients with IgG 4 -RD, a primarily fibrotic disorder in which the relevance of autoantibodies and T cells to fibrosis is still being explored. 5,38 Our recent studies have implicated antibodies to galectin-3 in a subset of patients with IgG 4 -RD, and others have identified autoantibodies to a recombinant truncated form of laminin 511, but definitive proof of a pathogenic role of these antibodies has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…4 A nationwide retrospective study revealed the efficacy of rituximab in patients with aggressive RRMS showing inflammatory activity despite second-line immunosuppressive therapies. 5 A retrospective multicentric Italian–Swiss study confirmed the strong efficacy of rituximab in reducing disease activity. 6 Finally, Naegelin et al evidenced that rituximab may significantly reduce the risk of disability progression in patients with secondary progressive MS. 7…”
Section: Introductionmentioning
confidence: 90%
“…Ferner lieferten zahlreiche retrospektive Analysen und eine Subgruppenanalyse Hinweise dafür, dass Rituximab sowohl effektiv bei aggressiver RMS bzw. progressiver MS sein kann [33][34][35][36][37][38][39] als auch den MS-Therapien der 1. Generation (i.e.…”
Section: Zusammenfassung • Abstractunclassified